Prevention of intestinal obstruction reveals progressive neurodegeneration in mutant TDP-43 (A315T) mice - Herdewyn, Sarah (BioMed Central, 2014)
BACKGROUND: Intraneuronal inclusions of TAR DNA-binding protein 43 (TDP-43) have been found in the majority of Amyotrophic Lateral Sclerosis (ALS) patients. Mutations in the gene encoding TDP-43 cause familial ALS. Transgenic mice expressing mutant TDP-43 with one such mutation (TDP-43 (A315T)) under control of the murine prion promoter develop motor symptoms, but their use is currently hampered by sudden death. We aimed to understand and overcome the cause of sudden death in TDP-43 (A315T) mice. Since intestinal obstruction was suspected to be the cause, intestinal motility of TDP-43 (A315T) mice was studied in an ex-vivo pellet propulsion assay. The effect on the enteric and motor phenotype was assessed, both in animals on normal chow or on a jellified fiber deprived diet, aimed at preventing intestinal obstruction. RESULTS: The frequency of the propulsive motor complexes was significantly reduced in the colon of TDP-43 (A315T) compared to non transgenic (NTG) mice. Immunohistochemistry revealed significant enlargement in size and reduction in number of the nitric oxide synthase (NOS) neurons in the myenteric plexus of TDP-43 (A315T) mice. Prevention of intestinal obstruction by jellified food abolished sudden death, allowing the motor phenotype to develop and slowly progress with a more pronounced degeneration of upper and lower motor axons. A downregulation of endogenous TDP-43 mRNA and protein levels was observed prior to neurodegeneration. CONCLUSION: TDP-43 (A315T) mice suffer from intestinal dysmotility due to degeneration of NOS neurons in the myenteric plexus. Feeding the mice jellified food prevents sudden death and allows the motor phenotype to progress.